Effects of mind-body exercise intervention on anxiety among women: a meta-analysis - Chen, Peng; Gu, Yusha; Shakila Mazalan, Nur; Koh, Denise; Du, Weiping; Luo, Yuanyuan (Frontiers in Psychology, 2025)
Objective:This meta-analysis aimed to evaluate the effectiveness of mind-body exercise (MBE) interventions in reducing anxiety among women and to explore potential intervention characteristics associated with greater efficacy.MethodsSeventeen studies involving 1,044 female participants were analyzed using Review Manager 5.3 and Stata 17.0. Subgroup analyses were conducted based on intervention type, weekly frequency, session duration, total intervention period, geographical region, and participant age. A random-effects model was applied to estimate pooled effect sizes and assess heterogeneity. The analysis adhered to Cochrane guidelines and was reported in accordance with the PRISMA checklist.ResultsMind-body exercise (MBE) interventions were associated with a significant reduction in anxiety symptoms among women, yielding a pooled standardized mean difference (SMD) of −1.14 [95% CI: (−1.56, −0.72), p < 0.00001]. However, substantial between-study heterogeneity was observed (I2 = 89%, Tau2 = 0.68), indicating considerable variability in effect sizes across studies. Among intervention types, Pilates showed the largest effect [SMD = −1.47, 95% CI: (−2.52, −0.41)], though this finding was based on only four studies and was accompanied by high heterogeneity (I2 = 93%), warranting cautious interpretation. Similarly, greater effects were observed for interventions involving 90-min sessions conducted three times per week over a period of 8–12 weeks [e.g., SMD = −1.46, 95% CI: (−2.18, −0.74)]. Nonetheless, these subgroup analyses also exhibited high heterogeneity (I2 values > 90%), suggesting that these parameters may not be universally optimal. Further subgroup analyses indicated stronger intervention effects in studies conducted outside China (SMD = −1.36, I2 = 93%) and among women aged 56 years and older (SMD = −1.30, I2 = 74%).ConclusionMind-body exercise interventions appear to have a substantial anxiolytic effect in women. However, these findings should be interpreted with caution due to the consistently high heterogeneity observed across analyses, as indicated by I2 values exceeding 85% in most subgroups and the presence of wide prediction intervals. Although certain formats, such as Pilates and intermediate-duration programs, show potential, further high-quality and culturally diverse trials are necessary to validate and refine intervention protocols.Systematic review registrationhttps://doi.org/10.37766/inplasy2025.6.0041.